H-point : the fundamentals of car design and packaging. - Macey, Stuart, ....-; Wardle, Geoff, ....- (Culver City : Designstudio, 2008)
The ultimate reference guide for car designers and automotive engineers! H-Point was written by the pioneer of the Vehicle Architecture course at Art Center College of Design, Stuart Macey along with the Director of Advanced Mobility Research, Geoff Wardle. Currently used as the educational handout for the transportation design students at Art Center, it will now be available to aspiring car creators everywhere, clearly organizing the packaging standards that apply to car and truck design; along with insightful graphic explanations, this book demystifies the automotive design process and allows designers access to an illustrious careers worth of knowledge.